The decorative structure in the calligraphic painting (Al-Academy, 2023)
The decoration structure in calligraphy painting is one of the variables that characterized the structure of the calligraphic composition due to the artistic, aesthetic and expressive properties of the letters of the Arabic calligraphy, which are represented by flexibility, compliance and the ability to form. Therefore, the researcher defined his problem by asking the following question: What is the decorative structure in the calligraphic painting? The study aimed to reveal the structure of the ornamentation in the calligraphy painting, while the researcher dealt with in the second chapter three sections, the first (the ornamental concept and meaning) and the second topic (the structural characteristics of the Arabic letter in the calligraphic calligraphy painting) and the third topic (the aesthetic foundations in the calligraphic calligraphy painting) and then Indicators of the theoretical framework and previous studies, while the third chapter dealt with the research procedures, where the researcher adopted the descriptive analytical approach of the research community and sampled it by 10%. (The ability of the Arabic letter and its response to formation contributed by employing it to produce calligraphic lettering paintings with lunar structures) and then recommendations to benefit from the results and findings of the research to support researchers, scholars and specialized colleges, and the researcher suggested a study (the formal significance of the trapping effect in the lettering calligraphy painting).